In vitro antibacterial and chemical properties of essential oils including native plants from Brazil against pathogenic and resistant bacteria - Barbosa, Lidiane Nunes [UNESP]; Probst, Isabella da Silva [UNESP]; Murbach Teles Andrade, Bruna Fernanda [UNESP]; Bergamo Alves, Fernanda Cristina [UNESP]; Albano, Mariana [UNESP]; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP]; Doyama, Julio Toshimi [UNESP]; Mores Rall, Vera Lucia [UNESP]; Fernandes Junior, Ary [UNESP] (Japan Oil Chemists Soc, 2015)
The antimicrobials products from plants have increased in importance due to the therapeutic potential in the treatment of infectious diseases. Therefore, we aimed to examine the chemical characterisation (GC-MS) of essential oils (EO) from seven plants and measure antibacterial activities against bacterial strains isolated from clinical human specimens (methicillin-resistant Staphylococcus aureus (MRSA) and sensitive (MSSA), Escherichia coli, Pseudomonas aeruginosa, Salmonella Typhimurium) and foods (Salmonella Enteritidis). Assays were performed using the minimal inhibitory concentration (MIC and MIC90%) (mg/mL) by agar dilution and time kill curve methods (log CFU/mL) to aiming synergism between EO. EO chemical analysis showed a predominance of terpenes and its derivatives. The highest antibacterial activities were with Cinnamomun zeylanicum (0.25 mg/mL on almost bacteria tested) and Caryophyllus aronzaticus EO (2.40 mg/mL on Salmonella Enteritidis), and the lowest activity was with Eugenia uniflora (from 50.80 mg/mL against MSSA to 92.40 mg/mL against both Salmonella sources and P aeruginosa) EO. The time kill curve assays revealed the occurrence of bactericide synergism in combinations of C. aromaticus and C. zeylanicum with Rosmarinus. officinalis. Thus, the antibacterial activities of the EO were large and this can also be explained by complex chemical composition of the oils tested in this study and the synergistic effect of these EO, yet requires further investigation because these interactions between the various chemical compounds can increase or reduce (antagonism effect) the inhibitory effect of essential oils against bacterial strains.
Keywords: GC-MS; Antibacterial activity; Terpenes; Plant secondary metabolites; Bacteria